Innovating Through Public–Private Partnership - Zai, Paul Vasile; Lazar, Andreea-Mihaela-Veronica (Archives of Business Research, 2024)
The article titled Innovating through Public-Private Partnership, explores the potential of public-private partnerships (PPP) as a means to foster innovation, economic stabilization, and sustainable community development. It highlights how the collaboration between public administration authorities and private or non-governmental sectors can address pressing societal challenges, including global warming, healthcare modernization, and technological advancements. The research outlines the essential components of PPPs, including financial models, management frameworks, and project evaluation criteria, with a particular focus on innovation-driven initiatives. Various stages of establishing a successful PPP are examined, from project conceptualization and partner selection to implementation and performance monitoring. Furthermore, the paper delves into the importance of funding methods and risk management, demonstrating how a well-structured PPP can combine public and private resources to deliver public goods effectively. The article also provides insights into sector-specific innovation strategies, such as digitalization and renewable energy projects. The case for renewable energy production through PPPs, involving solar and wind energy, is highlighted as a sustainable development model that strengthens collaboration between public and private sectors. By analyzing a five-year history of PPP projects in Europe and providing forecasts for the future, the paper underscores the growing relevance of PPPs in achieving long-term goals for economic and infrastructural development. The study concludes with recommendations for fostering a conducive environment for PPPs, such as legislative reform, the creation of national databases, and investment in education and training to enhance the success and innovation potential of PPPs.